Patient Experiences With Ambulatory Telehealth in Neurology: Results of a Mixed-Methods Study. Issue 6 (December 2021) - Olszewski, Carly; Thomson, Sharon; Strauss, Lauren; Graham, Rachel; Ezzeddine, Mustapha; Dodenhoff, Kristen; Ambrosini, Alexander; Smith, Laura Daniela; Silla, Laura; Schreiber, Allysen; Caraci, Caroline; Guzik, Amy; et al.
Abstract : Objective: To assess patient experiences with rapid implementation of ambulatory telehealth during the coronavirus disease 2019 (COVID-19) pandemic. Methods: A mixed-methods study was performed to characterize the patients' experience with neurology telehealth visits during the first 8 weeks of the COVID-19 response. Consecutive patients who completed a telehealth visit were contacted by telephone. Assenting patients completed a survey quantifying satisfaction with the visit followed by a semistructured telephone interview. Qualitative data were analyzed using the principles of thematic analysis. Results: A total of 2, 280 telehealth visits were performed, and 753 patients (33%) were reached for postvisit feedback. Of these, 47% of visits were by video and 53% by telephone. Satisfaction was high, with 77% of patients reporting that all needs were met, although only 51% would consider telehealth in the future. Qualitative themes were constructed, suggesting that positive patient experiences were associated not only with the elimination of commute time and associated costs but also with a positive physician interaction. Negative patient experiences were associated with the inability to complete the neurologic examination. Overall, patients tended to view telehealth as a tool that should augment, and not replace, in-person visits. Conclusion: In ambulatory telehealth, patients valued convenience, safety, and physician relationship. Barriers were observed but can be addressed.